The uses of fig (Ficus) by five ethnic minority communities in Southern Shan State, Myanmar - Aye Mya Mon; Yinxian Shi; Xuefei Yang; Pyae Phyo Hein; Thaung Naing Oo; Cory W. Whitney; Yongping Yang (BMC, 2020)
Abstract Background Most regions of Myanmar fall within the Indo-Burma Biodiversity Hotspot and are threatened with biodiversity loss. Development of a comprehensive framework for sustainable development is crucial. Figs are ecological keystone species within these regions and are also important for traditional spiritual food and health uses, which often have accompanying conservation practices. The traditional use and management of figs may offer clues to help guide the development of national policies for sustainable development. In this study, we showcase the rich ethnobotanical knowledge as well as the variety of collection and conservation practices of figs among five ethnic groups in Southern Shan State. Methods We performed both key informant and semi-structured interviews with 114 informants from five ethnic groups. Their uses for figs were categorized according to local practices and recipes. Informants were asked about trends in conservation status over the past 10 years and any conservation-related customs and practices. Data were analyzed quantitatively with common quantitative ethnobotany indices, the use report (UR) and use value (UV). Results Informants reported the uses of eight fig species (Ficus auricularta, F. concinna, F. geniculata, F. hispida, F. racemosa, F. religiosa, F. semicordata, and F. virens). F. geniculata and F. virens were most useful (UR = 228) and were used by all five ethnic groups, corresponding to a high use value (UV = 2). Treatments for 16 diseases were reported from seven species. Household consumption, economic and sacred uses were accompanied by sustainable practices of harvest and protection. Traditional taboos, in situ and ex situ conservation were common especially for highly demanded species (F. geniculata and F. virens) and the sacred fig F. religiosa. Conclusion Findings suggest that figs are useful for food (all informants) and medicine (13.16% of the informants) in the study area. Traditional taboos, in situ and ex situ conservation practices help to maintain sustainable utilization of locally important figs. This is an early contribution to the traditional knowledge of edible figs. Although similar uses have been reported in neighboring countries for seven of the fig species, the ethnobotanical use of F. concinna is novel.